2019
DOI: 10.1186/s12893-019-0501-0
|View full text |Cite
|
Sign up to set email alerts
|

Rate of intraoperative problems during sacroiliac screw removal: expect the unexpected

Abstract: Background The indications for sacroiliac screw (SI) removal have been under debate. Data on complication rates of SI screw removal is missing in the current literature. The objective of this study was to compare the rate of intra- and perioperative problems and complications during SI screw removal to those with SI screw fixation. Methods A retrospective observational study with two interventions in the same cohort was performed. Consecutive patients who underwent both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A complete IR may be necessary in the event of suspected infection or metal allergies, as well as in case of unexplained pain and/or explicit patient request. The aspect of removing the washer – "the Washer problem" – has already been described in the literature [ 15 , 16 ]. To combat these issues, an endoscopic SI IR approach was introduced in order to minimalize radiation exposure and soft tissue trauma [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete IR may be necessary in the event of suspected infection or metal allergies, as well as in case of unexplained pain and/or explicit patient request. The aspect of removing the washer – "the Washer problem" – has already been described in the literature [ 15 , 16 ]. To combat these issues, an endoscopic SI IR approach was introduced in order to minimalize radiation exposure and soft tissue trauma [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recovery of the washer can be the most difficult part of the procedure and may be the most time consuming aspect of an IR surgery. It has been described as challenging and as the aspect being most prone to problems [ 15 , 16 ]. Considering these adverse observations, alternative screw designs avoiding the use of a washer could be of benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Methods to accurately identify a specific entry point and aiming point for ideal screw position in each sacrum (perpendicular to SI joint) to avoid screw misplacement, reduce the operating time and radiation exposure have not been described yet. [19][20][21][22][23][24][25][26] In our study, the sacral bars were placed behind the sacrum away from the sacral nerve roots in a short operative time even in cases of sacral dysmorphism with minimal radiation exposure and the ability to do the technique in the emergency setting.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors even recommend implant removal routinely [ 8 , 15 ]. Due to the difficulty and proneness to intraoperative problems, the retrieval of the washer can be the most demanding part of the surgery and constitute the longest part of the surgery [ 16 , 17 ]. Therefore, Oberst et al suggested an endoscopic IR in order to reduce x-ray exposure and soft tissue damage [ 18 ].…”
Section: Introductionmentioning
confidence: 99%